Niraparib-induced STAT3 inhibition increases its antitumor effects - Zhao, Qianqian; Kohut, Adrian; Li, Yi-Jia; Martincuks, Antons; Austria, Theresa; Zhang, Chunyan; Santiago, Nicole Lugo; Borrero, Rosemarie Martinez; Phan, Xuan Thuy; Melstrom, Laleh; Rodriguez-Rodriguez, Lorna; Yu, Hua (Frontiers in Oncology, 2022)
Recently, poly(ADP-ribosyl)ation polymerase inhibitors (PARPis), which induce synthetic lethality of tumor cells with DNA damage repair defects, have emerged as a promising therapy for ovarian, breast, and pancreatic cancer. Although the PARPi Olaparib is limited to treating cancer patients with DNA repair deficiencies, the PARPi Niraparib is FDA approved to treat ovarian cancer patients regardless of their status in DNA repair pathways. Despite differences in the affinity to PARP enzymes, the rationale behind the clinical use of Niraparib in patients without DNA repair deficiencies is still lacking. Moreover, only Olaparib has been approved for pancreatic ductal adenocarcinoma (PDAC) patients with BRCA mutations, accounting for only 5-7% of total PDACs. It remains unclear whether Niraparib could be beneficial to PDACs without BRCA mutations. We found that Niraparib inhibits ovarian and PDAC tumor cell growth, regardless of BRCA mutational status, more effectively than Olaparib. Unlike Olaparib, which is known to activate STAT3, Niraparib inhibits STAT3 activity in ovarian and PDAC cancer cell lines and patient tumors. Moreover, Niraparib regulates the expression of several STAT3 downstream genes involved in apoptosis. Overexpression of a constitutively activated STAT3 mutant rescues Niraparib-induced cancer cell apoptosis. Our results suggest that Niraparib inhibits pSTAT3 by interfering with SRC tyrosine kinase. Collectively, our studies provide a mechanism underlying Niraparib’s ability to induce tumor cell apoptosis without BRCA mutations, suggesting the potential use of Niraparib for treating PDAC patients regardless of BRCA status.